Records management policy: is it a technical question of interoperability? - García-Morales, Elisa (Anuario ThinkEPI, 2013)
This article questions the appropriateness of considering records management policy in the regulatory context of the National Interoperability Framework, thereby reducing it to a technical question limited to electronic documents. A records management policy is a strategic issue of key importance in the context of e-Government projects.
Keywords: Records management policy; NTI; Open government interoperability; Spain; ISO 30300; ISO 15489; e-Administration.